Recovery of α-lactalbumin from whey protein isolate and osteopontin from milk by anion exchangers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Chemistry at Massey University, New Zealand - Chen, Yishan (Massey University, 1998)
A series of amines, DMEA, DMH, DMO, DMD, DMDo, and Do, were coupled to Sepharose, which was activated by epichlorohydrin first, to prepare amino anion exchangers DMEA-Seph, DMH-Seph, DMO-Seph, DMD-Seph, DMDo-Seph, and Do-Seph. The batch binding of α-lactalbumin and ß-lactoglobulin in 25 mM NaCl at around proteins' IEP to these exchangers and a commercial anion exchanger Q-Seph-ff were tested. Q-Seph-ff, DMEA-Seph, DMH-Seph, and DMO-Seph bound both of proteins at pH > IEP. Q-Seph-ff, DMEA-Seph, DMH-Seph did not bind either of the proteins at pH < IEP. DMO-Seph, DMD-Seph, DMDo-Seph, and Do-Seph bound both of the proteins, especially α-lactalbumin, by hydrophobic interaction at and below the proteins' IEP. The proteins bound by these exchangers except DMO-Seph could not eluted by HCl at low pH. HCI at pH 2.5 could be used to elute these proteins from DMO-Seph. Recovery of α-lactalbumin from WPI in 25 mM NaCl at pH 3.8-5 by DMO-Seph, DMD-Seph, DMDo-Seph, and Do-Seph were tested. These exchangers were able to bind α-lactalbumin in preference to ß-lactoglobulin at and below the proteins' IEPs. Thus DMD-Seph gave an α-lactalbumin yield and purity of 70 and 80% at pH 4.3, DMO-Seph 77 and 81% at pH 4.4. However DMD-Seph had difficulty in eluting all of the α-lactalbumin unless using ethanol. The batch binding of α-lactalbumin and ß-lactoglobulin in high concentration of NaCl at low pH (2.5) by DMO-Seph was tested. The exchanger showed strong hydrophobic affinity for a-lactalbumin but not ß-lactoglobulin in 200-500 mM NaCl. Recovery of native α-Iactalbumin from WPI in 400 mM NaCl at pH 2.5 by DMO-Seph was tested. This gave an α-lactalbumin yield and purity of 79 and 73% and a capacity of DMO-Seph 0.73 g/g in 400 mM NaCl at pH 2.5, compared to 67%, 84% and 16 mg/g of DMO-Cell. DMO-Cell was prepared. Cellulose was modified by propyl oxide and epichlorohydrin and then activated by ECH. The activated cellulose was then coupled with DMO. The effects of cellulose particle size, cellulose type and substitution level of DMO-Cell on binding of whey proteins were investigated. DMO-Cell, activated by 1,4-butanediol diglycidyl ether, with substitution level 0.55 meq/g was prepared. It showed a better binding capacity than DMO-Cell activated by epichlorohydrin. Recovery of native α-lactalbumin from different WPI in 400 mM NaCl at pH 2.5 by DMO-Cell was tested. DMO-Cell showed good selectivity for α-lactalbumin from all of three WPI. This gave an α-lactalbumin yield and purity of 13.5 mg/g from WPI (PT8253). From a low α-lactalbumin content WPI this gave an α-lactalbumin yield and purity of 70 and 91%.
Keywords: Milk proteins; Whey products; Genetic aspects; 0305 Organic Chemistry